Anti-Atherogenic Role of Peroxisome Proliferator-Activated Receptor Ligands - Nigro, Julie; Ballinger, Mandy L.; Osman, Narin; Dart, Anthony M.; Little, Peter J. (Current Cardiology Reviews, 2005)
Two families of peroxisome proliferating-activated receptor (PPAR) ligands are utilized clinically to address abnormalities of blood-borne cardiovascular risk factors. PPAR-α ligands, the fibrates, lower plasma triglycerides and increase high-density lipoprotein (HDL)-cholesterol leading to positive outcomes in clinical trials such as the Veterans Affairs HDL Intervention Trial. PPAR-γ ligands, the recently introduced family of thiazolidinediones, act as insulin sensitizers to alleviate the hyperglycemia of insulin resistant states such as Type 2 diabetes. The primary aim of treating the cardiovascular risk factors is to reduce the burden of cardiovascular disease, mostly atherosclerotic vascular disease. Considerable evidence is emerging that PPAR ligands can exert anti-atherogenic activity. Although the agents acting on their target nuclear receptors are primarily regulators of gene transcription it may be that some actions are independent of gene transcription and represent direct inhibition of atherogenic signalling pathways in the vasculature. The direct actions including inhibition of vascular smooth muscle cell proliferation and inhibition of glycosaminoglycan elongation on proteoglycans, the latter leading to reduced low-density lipoprotein (LDL) binding, provide in vitro examples of antiatherogenic actions. PPAR ligands reduce atherosclerosis in animal models such as the ApoE-null mouse and PPAR-γ attenuate in-stent restenosis in patients with diabetes. The actions of these agents have lead to suggestions that they may be useful in vascular therapy even in the absence of the underlying risk factor abnormality. However, they may also represent tools and provide insights into areas where agents directly targeting atherosclerotic mechanisms may be developed to provide combined therapy with agents targeting traditional risk factors.
Keywords: peroxisome proliferating activated receptor (ppar)